THE EARLY DETECTION OF METABOLIC SYNDROME USED NCEP ATP-III METHOD IN WAAI VILLAGE COMMUNITY CENTRAL MALUKU REGENCY - Theosobia Grace Orno (Molucca Medica, 2022)
Metabolic syndrome is a metabolic disorder that complexly includes carbohydrate, lipid and protein metabolism disorders which are known to be the main cause of diabetes mellitus, hypertension and coronary heart disease. Waai Village, Central Maluku Regency is one of the villages affected by the earthquake for a long time so that social assistance in the form of fast food is consumed in the long term which is thought to be one of the causes of metabolic syndrome. The purpose of this research is to detect the presence of metabolic syndrome with the NCEP ATP-III criteria consists of measuring blood pressure, fasting blood glucose levels and serum triglyceride levels using the photometric method. This type of research is descriptive research with a cross sectional approach. The sampling technique used is purposive sampling, in accordance with the predetermined sample criteria. The results showed that 29 of 50 subjects (58%) had metabolic syndrome with an average blood pressure of 148/94 mmHg, an average fasting blood glucose level of 158 mg/dL, and an average triglyceride level of 198 mg/dL.